2006
DOI: 10.1002/ejic.200500986
|View full text |Cite
|
Sign up to set email alerts
|

Methyl‐Hydroxypyridinecarboxylic Acids as Possible Bidentate Chelating Agents for Aluminium(III): Synthesis and Metal–Ligand Solution Chemistry

Abstract: In view of a possible application to aluminium chelation therapy, 1-methyl-3-hydroxy-4-pyridinecarboxylic acid (1M3H4P) and 1-methyl-4-hydroxy-3-pyridinecarboxylic acid (1M4H3P) were synthesized, and their chemical interactions with aluminium(III) were investigated in aqueous 0.6 m (Na)Cl at 25°C by means of potentiometric titrations. The qualitative and quantitative results obtained were confirmed by UV spectrophotometry and 1 H NMR spectroscopy. For both ligands, the species AlL 2+ , AlL 2 + , AlL 3 , and Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…The pKa values increase by ca. 0.2 log units when passing from (Na)Cl 0.6 m to KCl 0.2 M ionic strength.The low pKa values for the phenolic-OH, based on the comparison with salicylic acid derivatives, was justified[20], and it agrees with values obtained for the other HPCs[4].…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The pKa values increase by ca. 0.2 log units when passing from (Na)Cl 0.6 m to KCl 0.2 M ionic strength.The low pKa values for the phenolic-OH, based on the comparison with salicylic acid derivatives, was justified[20], and it agrees with values obtained for the other HPCs[4].…”
supporting
confidence: 84%
“…see [20]). Broadening can be attributed [20] to the formation of several isomers (up to 4 and 2 diastereoisomers can exist in solution for the bis-and tris-complexes, respectively) and to a relatively slow kinetics of interconversion between them.…”
Section: Metal/ligand Complexesmentioning
confidence: 96%
“…Chemicals HPCs were synthesized as described in ref. [16][17][18], except L5 and L6 which were synthesized according to the procedure reported in the next section. The CuCl 2 stock solution was prepared from CuCl 2 Á2H 2 O (Sigma-Aldrich) dissolved in doubly distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The protonation steps of the HPC ligands have been determined by pH-potentiometry, either in the present study (L5 and L6) or in previous ones (all other HPCs [16][17][18] ). The constants are collected in Table 1.…”
Section: Proton Dissociation Processes Of the Ligands In Solutionmentioning
confidence: 99%
“…Numerous studies on the design, synthesis and complex formation equilibria of variously substituted hydroxypyridinecarboxylic acids have been presented by the group of Di Marco: these ligands are characterized by two coordinating groups (-OH and -COOH) in various positions (2,3; 3,2; 3,4; 4,3) and differently methylated. [50][51][52][53][54][55] A study of our group on bisphosphonate ligands showed their high efficiency as iron chelating agents, reaching pFe values higher than that of deferiprone. 56 To further improve bisphosphonate chelating properties the conjugation with other strong coordinating groups was proposed.…”
Section: Recent Research Achievements On Iron Chelating Agentsmentioning
confidence: 99%